Signal and image multiresolution analysis - Ouahabi, Abdeldjalil (London : ISTE ; Hoboken, N.J. : Wiley, 2012)
Multiresolution analysis using the wavelet transform has received considerable attention in recent years by researchers in the fields of computer graphics, geometric modeling, visualization, signal and image processing, biomedical engineering, telecommunication. Multiresolution analysis is a powerful tool for efficiently representing signals and images at multiple levels-of-detail with many inherent advantages, including compression, level-of-details display, progressive transmission, level-of-details editing, filtering, modeling, fractals and multifracatls--
Includes bibliographical references and index.
Keywords: Image processing -- Mathematical models; Signal processing -- Mathematical models; Resolution (Optics); Wavelets (Mathematics)